2016
DOI: 10.1007/s11064-016-1982-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of the LRRK2 Kinase Inhibitor PF-06447475 in Human Nerve-Like Differentiated Cells Exposed to Oxidative Stress Stimuli: Implications for Parkinson’s Disease

Abstract: Leucine-rich repeat kinase 2 (LRRK2) has been implicated in oxidative stress (OS) and neurodegeneration in Parkinson's disease (PD). However, the pathophysiological mechanism of the LRRK2 kinase in neurons under stress stimuli is not yet understood. We demonstrate that rotenone (ROT), a mitochondria complex I inhibitor frequently used to generate in vitro and in vivo experimental models of PD, induces LRRK2 phosphorylation at serine 935 p-(S935) concomitant with cell death in nerve-like differentiated cells (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…Mitochondria are important intercellular organelles in the nerve cells, producing energy through the mitochondrial respiratory chain and acting as a mediator of the cell survival and death (Keilhoff et al, 2016 ; Mendivil-Perez et al, 2016 ). Accumulating studies of PD animals and PD patients suggested that mitochondrial dysfunction may play crucial roles in the PD pathogenesis (Martin, 2006 ; Desmet et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are important intercellular organelles in the nerve cells, producing energy through the mitochondrial respiratory chain and acting as a mediator of the cell survival and death (Keilhoff et al, 2016 ; Mendivil-Perez et al, 2016 ). Accumulating studies of PD animals and PD patients suggested that mitochondrial dysfunction may play crucial roles in the PD pathogenesis (Martin, 2006 ; Desmet et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rotenone (ROT) introduction into nerve-like differentiated cells generates in-vitro models of PD, resulting in LRRK2 phosphorylation at Ser935, nuclear condensation, increased nuclear factor κ-light-chain-enhancer of activated B (NF-κB) expression, and activated caspase-3. Subsequent exposure to PF-06447475 blocks LRRK2 phosphorylation at Ser935 and reverses the apoptotic signaling activated by ROT [66]. In 2 preclinical mouse models of LRRK2 (bacterial artificial chromosome transgenic hG2019S and hR1441G), GNE-7915 was reported to enhance DA release and synaptic vesicle recycling [67].…”
Section: Lrrk2 As a Therapeutic Targetmentioning
confidence: 99%
“…We first evaluated whether the PSEN1 E280A mutation affects the capacity of MSCs to generate mesodermal and ectodermal lineages through differentiation and transdifferentiation, respectively. Therefore, WJ-MSCs were isolated from ten umbilical cords of volunteers according to standard procedures [39], and PCR-RFLP electrophoretic profile analysis identified one umbilical cord sample out of ten as a carrier of the mutation PSEN1 c.839A > C, p.E280A (PSEN1 E280A MSCs). Then, PSEN1 E280A MSCs and wild-type WJ-MSCs (WT PSEN1 MSCs) were further cultured and characterized for morphological, karyotype, immuno-phenotypic features and differentiation capabilities.…”
Section: Psen1 E280a and Wild-type Wj-mscs Show Similar Phenotypic Imentioning
confidence: 99%